Agricultura familiar e o desenvolvimento das agroindústrias familiares rurais: panorama, indicadores e potencialidades no Oeste do Paraná - Besen , Fabíola Graciele (2021)
Among the projects in the dynamics of the rural environment are the rural family agroindustries (AFR). AFR is present in discussions on the transformations of the Brazilian rural environment, especially in issues related to the environment, new technologies and the need for greater value addition to agro-industrialized products, both for the domestic and foreign markets. The rural family agroindustry is an income alternative for small rural producers, as agro industrializes the primary products produced by the family. the rural family agroindustry produces its raw material or acquires a small quantity from neighboring farmers and its workforce is predominantly family owned. The general objective of this study is to analyze the context of transformation and/or agro-industrialization in Rural Family Units (UFR) in the western mesoregion of Paraná and to propose improvements to the management procedures of rural family agribusinesses. The research is characterized as a descriptive study, with a quantitative approach and secondary sources extracted from the database of the reports of the "organic agriculture project in BP3", work conducted and developed by BIOLABORE - cooperative work and technical assistance of Paraná, together with the binational Itaipu. the information was extracted from the reports of 168 family farming units with rural family agribusiness in this region. The scenario of these agro-industries is present in graphs, tables, charts, figures and enabled an assessment and elaboration of indicators aimed at improving the points that can improve the performance of the AFR. The set of indicators, however, with the use of management tools aimed at decision-making, choice of priorities and influence that one exerts over the other and/or others, guide the actions to be taken in agribusiness. The work with a broad coverage of the reality of each agroindustry resulted in directions and actions for agroindustries to strengthen them, whether individually or in an associative/cooperative manner. aspects related to agribusiness, their production processes, technologies, innovations and opportunities to leverage markets through their effectiveness are contemplated in the application of the indicators by the tools used and the proposed actions, are aimed at structuring and improving the opportunities of the UFR through their AFR in the rural environment of this noble mesoregion of Western Paraná.